Determinants of The Expenditure of Tourist Demand in Coastal Destinations - Tanana, Ariadna Belén (2022)
The aim of this work is to analyze the determinants of tourist expenditure in Monte Hermoso, a destination located in the southwest of the province of Buenos Aires, Argentina. Tourist surveys were administered during the austral summer (January-February) and considered as primary information. Socioeconomic and trip-related variables were selected to explain the determinants of the average total expenditure of tourists in this destination. The Ordinary Least Squares (OLS) method was applied. From the results obtained, it was determined that the level of income, origin, group size, and type of accommodation are the regressors that best demonstrate the spending behavior of the destination's domestic demand. Therefore, it is possible to identify the most attractive demand segments that contribute to improving competitiveness and increasing the rate of return of the destination.